Notes on the avifauna of Bacan, Kasiruta and Obi, North Moluccas - Frank R Lambert (Indonesian Ornithologists’ Union, 1994)
In 1991 and 1992, field work was conducted in the north Moluccas under the he auspices of IUCN (the World Conservation Union) to ascertain the status of three species of parrot: White Cockatoo Cacatua alba, Chattering Lory Lorius garrulus and two subspecies of Violet-backed Lory Eos squamata riciniata and E. s. obiensis (Lambert 1993; in press). During these survey, about one month was spent on Bacan October/November 1991), four day on the adjacent island of Kasiruta (November 1991) and a further month on Obi (February 1992). Most of the parrot surveys were conducted in the lowlands and hills, although observations were made up to 1,300 m on the steep forested western slopes of Mt Sibela, Bacan, and at altitudes of up ca. 730 m in the upper catchment of the Widi Besar River, Obi. Even at these higher altitudes, however, the forest was tall, with trees estimated to be 30-35 m tall, and best described as submontane rather than montane even at 1,300 m. Unfortunately, it was not possible to reach the true montane forests of Mt Sibela (maximum elevation 2111m).